The value of nonlinear control theory in investigating the underlying dynamics and resilience of a grocery supply chain. Issue 1 (2nd January 2016) - Spiegler, V.L.M.; Potter, A.T.; Naim, M.M.; Towill, D.R.
Abstract : In an empirical context, a method to use nonlinear control theory in the dynamic analysis of supply chain resilience is developed and tested. The method utilises block diagram development, transfer function formulation, describing function representation of nonlinearities and simulation. Using both 'shock' or step response and 'filter' or frequency response lenses, a system dynamics model is created to analyse the resilience performance of a distribution centre replenishment system at a large grocery retailer. Potential risks for the retailer's resilience performance include the possibility of a mismatch between supply and demand, as well as serving the store inefficiently and causing on-shelf stock-outs. Thus, resilience is determined by investigating the dynamic behaviour of stock and shipment responses. The method allows insights into the nonlinear system control structures that would not be evident using simulation alone, including a better understanding of the influence of control parameters on dynamic behaviour, the identification of inventory offsets potentially leading to 'drift', the impact of nonlinearities on supply chain performance and the minimisation of simulation experiments.